Ways to improve the mechanism of direct taxation of commercial banks based on advanced foreign practices. - L.Ergasheva (Academia One Publishing, 2025)
The stable operation of the banking system is fundamentally important for the entire economy. As such, bank taxation should be directed toward ensuring the stability of the banking system. While various regulatory and tax measures have been implemented, a discussion continues about unanswered questions, particularly concerning macro-prudential effects linked to systemic risks and negative micro-prudential externalities stemming from limited liability and asymmetric information. This issue has become a pressing concern for policymakers, academics, and international regulatory bodies. This paper examines the current state of commercial bank taxation in Uzbekistan and proposes a new approach based on advanced foreign practices, specifically from Japan and China, as well as the United States, Germany, and France. The study employs a comparative-analytical method, using data from commercial banks in these countries to develop a framework for implementing a direct bank taxation theory in Uzbekistan. The findings suggest that a well-structured system of direct bank taxes can support fiscal stability while promoting financial integrity and investment activity. The paper concludes with project-based solutions for implementing a direct bank taxation mechanism in Uzbekistan, including the use of an IT-based "tax-rating system" and the integration of automated information systems for real-time monitoring
Keywords: integrity; Germany; bank taxes; financial integrity